Preliminary Report on War-Damaged Cities and Sites in South-Western and Western Iran - Charlesworth, Martin
Susa, Dezful, Hoveyzeh, Il?m, ??leh-?b?d, Seyyed Hasan, Darreh Shahr, Kerm?nsh?h (B?khtar?n), Qa?r-i Sh?r?n, Sar-i Pol-i Zoh?b